Adenia hondala-derived Biopolymer Nanoparticles Cause G2/M Cell Cycle Arrest in Breast Cancer Cells - Varadharajaperumal, Pradeepa; Muthuswamy, Sujatha; Pothagar, Devi; Ganesan, Mareeswari; Santhanam, Amutha (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Silver nanoparticles (AgNPs) are a type of nanomaterials known for their antimicrobial and disinfectant properties due to their detrimental effects on targeted cells. This study investigated the delivery of a novel therapeutic system based on chitosan-coated silver nanoparticles (Ch-Ag NPs) for Tamoxifen to MCF-7 human breast cancer cells. The Ag NPs were synthesized from Adenia hondala tuber extract and coated with chitosan to form Ch-Ag NPs. Tamoxifen was loaded onto these nanoparticles to create Tam-Ch-AgNPs, functioning as a drug delivery system. Apoptosis induction was confirmed through annexin V staining and analysis of mitochondrial membrane potential. Cell cycle analysis showed G2/M phase arrest in Tam-Ch-AgNPs-treated cells, indicating apoptosis induction. The inhibition of cancer cell growth by Tam-Ch-AgNPs suggests potential for developing eco-friendly therapeutic agents in nano medicine, particularly for cancer treatment, prompting further research in this field.